Patient-level and system-level barriers associated with treatment delays for ST elevation myocardial infarction in China. Issue 19 (24th June 2020) - Yin, Xuejun; He, Yibo; Zhang, Jing; Song, Feier; Liu, Jin; Sun, Guoli; Liang, Yan; Ye, Jianfeng; Hu, Yunzhao; Song, Mingcai; Chen, Cong; Xu, Qingbo; et al.
Abstract : Objective: This study aims to understand the current ST elevated myocardial infarction (STEMI) treatment process in Guangdong Province and explore patient-level and system-level barriers associated with delay in STEMI treatment, so as to provide recommendations for improvement. Methods: This is a qualitative study. Data were collected using semistructured, face-to-face individual interviews from April 2018 to January 2019. Participants included patients with STEMI, cardiologists and nurses from hospitals, emergency department doctors, primary healthcare providers, local health governors, and coordinators at the emergency medical system (EMS). An inductive thematic analysis was adopted to generate overarching themes and subthemes for potential causes of STEMI treatment delay. The WHO framework for people-centred integrated health services was used to frame recommendations for improving the health system. Results: Thirty-two participants were interviewed. Patient-level barriers included poor knowledge in recognising STEMI symptoms and not calling EMS when symptoms occurred. Limited capacity of health professionals in hospitals below the tertiary level and lack of coordination between hospitals of different levels were identified as the main system-level barriers. Five recommendations were provided: (1) enhance public health education; (2) strengthen primary healthcare workforce; (3) increase EMS capacity; (4) establish an integrated care model; and (5) harness government's responsibilities. Conclusions: Barriers associated with delay in STEMI treatment were identified at both patient and system levels. The results of this study provide a useful evidence base for future intervention development to improve the quality of STEMI treatment and patient outcomes in China and other countries in a similar situation.